Environmental Concern and the theory of planned behaviour: Identifying the green consumer. - De Jager, JNW (Department of Environmental and Geographical Science, 2014)
Since the 1980's environmentalism has developed into a major worldwide movement with concern for the environment having grown exponentially over the last two decades. With this change in thinking there have been corresponding shifts in consumer attitudes with many stating they are willing to pay more for eco-labelled products and services. With the increase in consumer demands on protection of the environment and businesses becoming aware of their responsibility towards the objective of sustainability, retailers and manufacturers have moved beyond simply addressing environmental regulatory issues and are introducing alternative products that could be classified as ecofriendly. However, at present, businesses find it difficult to predict consumers' reaction towards these products with a degree of accuracy that is necessary to enable the development of new targeting and segmenting strategies. This presumably has contributed towards several failures in green products development (D'Souza et al, 2007). This study tested whether the Theory of Planned Behavior (TPB; Ajzen, 1991) explains consumers' intention to purchase eco-friendly products (EFPs). The researcher extended the TPB by including environmental concern in the model. The aim is to test whether this construct directly influences people's attitudes towards the purchase of these products. Furthermore, the study investigates whether consumers' search for information on EFPs and whether their price/quality sensitivity may also affect their intention to purchase these products. The respondent base is then divided by means of demographic segmentation in order to determine whether attitudes towards and intention to purchase EFPs differ between age, income and gender groups. A survey was conducted among 100 customers of a well-known retailer, known for its selection of EFPs. The data obtained was analysed using SPSS software. The results found the TPB to be valid within an environmentally responsible purchase decision framework and that environmental concern does influence consumer attitudes towards the purchase of EFPs. This is in line with the findings of De Groot & Steg (2007) and Bamberg (2003) which also found that ii environmental concern should not be seen as a direct determinant of behaviour, but an important indirect one. The emphasis should thus be on increasing consumers' level of environmental concern and then identify those consumers with favourable attitudes towards EFPs, rather than identify green consumers solely on the basis of environmental concern. Furthermore, the study found that consumers' search for information and trust in product labelling affect their intention to purchase these products. This study suggests that the consumer ought to be educated on the differences between EFPs and regular products by means of advertising and label information. It also emphasises the need for claims made about EFPs to be substantiated. With regards to price and quality sensitivity, the results show that both these constructs affect consumers' attitudes towards and intention to purchase EFPs. Consumers will not readily buy an EFP if it is somewhat more expensive than a regular product and they are even less likely to purchase such a product if it does not meet the same quality standards. With regards to demographic segmentation, the results show that women are more environmentally concerned than men and also have a greater intention to purchase EFPs in future. There is no difference between age groups in terms of their attitudes and intention to purchase EFPs but those aged 41-60 have greater volitional control over the purchase of these products as they are better able to afford them. Similarly, income groups show no difference in attitudes and intention but higher incomes groups have greater volitional control over the purchase of EFPs. Nevertheless, there was no difference found between age and income groups in terms of their price sensitivity. This brings into question the effectiveness of the premium pricing strategy currently employed by many manufacturers of EFPs as it seems that people with higher incomes, even though they are better able to afford EFPs, are not more willing to purchase these products if priced higher than regular products.